MISTAKES IN DEALING WITH AORTIC DISSECTION. LESSONS FROM THREE WARNING CASES. - Marek, Dan; Nemec, Petr; Herman, Miroslav; Gwozdziewicz, Marek; Troubil, Martin; Lukl, Jan (Biomedical papers, 2008)
BACKGROUND: Aortic dissection is a dangerous condition with a high mortality in the acute stage. Aortic dissection requires early diagnosis and treatment.METHODS AND RESULTS: This short review discusses and focuses on known complications of aortic dissection and its natural mortality applying data from already published reports and from cohorts and registers, especially IRAD. Survival data of patients with type A and type B of dissection are presented and treatment options are proposed. The review presents three interesting cases from our database pointing out mistakes made in the diagnostic process and in dealing with the patient even after establishing the correct diagnosis. In one case, a patient with chest pain + ``immeasurable'' BP was suspected to suffer from an acute myocardial infarction and cardiogenic shock instead of AoD + aortic branch obstruction. In another patient with chest pain + V1V2 ST elevation, again the acute coronary syndrome was suspected. In fact, AoD with a perforation to cardiac chambers through the interventricular septum was the explanation. In the third case, the correct diagnosis of AoD was established. This patient was at a significant risk of aortic rupture because of his uncontrolled blood pressure. Instead of sedation administration and effective BP lowering, the patient was stressed even more by detailed information about this life threatening disease. This led to an aortic rupture with cardiac tamponade. Other mistakes made when dealing with all these presented cases are also discussed.CONCLUSION: The high mortality in patients suffering from aortic dissection is often potentiated by misdiagnosing and mishandling of these patients in clinical scenario.
Keywords: Aortic dissection/Complications/Diagnosis/Treatment/Mistakes